An exploration of the relationship between Chinese job applicants’ individual attitudes toward CSR and their job choices - GENG, HAO (2019)
The study aims to investigate Chinese job applicants’ individual attitudes toward CSR and how they make their job choice intentions. The study also explores whether there is any understanding of relationships between Chinese job applicants’ individual attitudes toward CSR and their job choices. The main sample of this study focuses on the Nottingham University Chinese students especially Business School students, and the data was collected from a sample of 105 Chinese respondents by online questionnaires. This study adopted the Likert Scales to measure respondents’ individual attitudes toward CSR and their job choice intentions, and the relationship between them was tested by the Linear Regression. There are three major findings in this study: 1) Most Chinese job applicants hold a positive attitude toward CSR; 2) Most Chinese job applicants would consider the CSR when making job choice decisions; 3) Chinese job applicants’ individual attitudes toward CSR are strongly associated with their job choices. Moreover, positive attitudes among job applicants toward CSR will result in their relevant job choices. The meanings of these findings and the possible reasons behind these findings are elaborated. The contribution of this study to literature and practice are discussed. Recommendations of this study for future research are provided.